APTA Geriatrics' Guiding Principles for Best Practices in Geriatric Physical Therapy: An Executive Summary. Issue 2 (15th April 2022) - Criss, Michelle G.; Wingood, Mariana; Staples, William H.; Southard, Veronica; Miller, Kenneth L.; Norris, Traci L.; Avers, Dale; Ciolek, Cathy H.; Lewis, Carole B.; Strunk, Ellen R.
Abstract : Geriatric physical therapy requires a unique skill set and knowledge to provide best practice care. The skill set requires clinicians to recognize the significance of the continuum of aging from optimal to pathology-influenced aging and how psychosocial, environmental, behavioral, accessibility, and economic factors affect this aging continuum, optimal health, and wellness. Employing this distinctive skill set while also utilizing evidence-based practice, acknowledging the variability observed in older adults, and utilizing interwoven care systems that impact outcomes are key characteristics of best practice. The Academy of Geriatric Physical Therapy developed best practice guidelines consisting of 6 principles needed to ensure patients receive the care that they deserve. Best practice principles include person-centered care, anti-ageist beliefs, holistic assessment using sound outcome measures, evidence-based interventions, physical activity promotion, and interprofessional collaborative practice. This executive summary presents these principles along with suggested action steps for each element of best practice. The aims are to encourage individual self-assessment, promote improvement in practice on an individual and facility/system level, increase communication and collaboration with other health care providers about global best practices for older adults, and to further target education, resources, and advocacy toward achieving best practice on a larger scale.